FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA SAHAM PERUSAHAAN AGRIBISNIS DI BURSA EFEK JAKARTA: PENDEKATAN STRUCTURAL EQUATION MODELLING - MADE ANTARA; PUTU INDAH LESTARI (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2008)
Capital Market is a market which is for many long term monetary instrumentsthat can be sold and bought. The capital market has major functions for the economysystem of a country because it functions for rising up the efficiency in an economysystem by connecting money from investor to the company. This present researchintended to know how much may effects of macro and micro in agribusiness companystock performance in Jakarta Stock Exchange, JSX (now: Indonesiaq Stock Exchange,ISE)). The location of this research was done by purposive sampling. The data wascollected by using a study documentation which means learning some documents ofmuch agribusiness company which was taken from JSX Monthly Statistics. The datawas analysed by using Structural Equation Modelling (SEM) method which means byan integrated analysis, consist of correlation analysis (regression and correlation), theapplication of structural mode, path analysis, and factor analysis. The measure processwill use the SPSS 12.0 for windows and Amos 4.01 program.By analysis the data, the result of it are the factor that effect the stockperformance are macro and micro. Macro consists of exchange-rate, inflation, andinterests. Micro consist Earning per Share (EPS), Net Profit Margin (NPM), PriceEarning Ratio (PER), Rate Return of Investement (ROI), dan Return of Equity (ROE).Besides, the stock performance also affect the price of stock, devidend, and volumetrade. Macro direclty affect the stock performance for 0,037. but micro affect the stockperformance for 0,033.The investor who will invest their money in capital market need to care for thefluctuation of interest because, the interest has many effect based on the data analysisabove. In micro, the investor need to care for the EPS value because the high EPSshows any probability will be higher in turn of invest.